(untitled) (Tempo e Argumento, 2021)
Few studies in Colombia have been interested in historical relations between legal medicine and psychiatry/mental medicine. The medico legal studies concerning psychiatric expert exhibitions constitute a good source of information to analyze these relationships. The discourse about mental illness in the legal field and the medicalization of justice allows us to analyze the role of psychiatric experts, and the definition of criminals categorized as alienated. Additionally, these same studies allow us to analyze the functionality of somatic and psychological examinations to define the state of alienation and the mode of treatment of these criminals. Using the medical-legal studies of the coroner Julio Ortiz Velásquez published in 1953, this article analyzes the forensic psychiatric discourses in the first half of the twentieth century in Colombia. Keywords: Medical-legal study; Mental illness; Psychiatric expertise; Colombia.